Kabalistyczna egzegeza opowiadania "Śmierć i busola" Jorge Luisa Borgesa - Moreno-Szypowska, Jadwiga Clea (Załącznik Kulturoznawczy, 2023)
Kabbalistic Exegesis of Death and the Compass by Jorge Luis Borges This article seeks to decipher Jorge Luis Borges’ short story Death and the Compass in a Kabbalistic spirit. The author shows how the Argentine writer uses various methods of Jewish hermeneutics. A detailed analysis of selected elements of the story, such as names, time, place, geographic directions, colors, geometric figures, types of plants, or words used by Borges, leads to a surprising interpretation of the story, in which what is important is not just solving the murder mystery, but showing the inverted relationship between the seeker and the sought. In Borges’ hands, Kabbalah—whose purpose is to bring one closer to God—loses its religious overtones and becomes a creative tool for writing a successful story. Thus, the most important current of Jewish mysticism leaves the realm of faith to enter the realm of the ludic, where man and the devil play cops and villains.